Ein Futurelab für die Medienpädagogik - Knaus, T.; Meister, Dorothee M.; Narr, K. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Qualitätsentwicklung – Professionalisierung – Standards. Thesen aus medienpädagogischer Sicht - Knaus, T.; Meister, Dorothee M.; Tulodziecki, G. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Digitalisierung erfordert professionelle medienpädagogische Unterstützung - Knaus, T.; Meister, Dorothee M.; Narr, K. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Quality Development – Professionalization – Standards. A Mediapedagogy Futurelab - Knaus, T.; Meister, Dorothee M.; Tulodziecki, G. (Futurelab Medienpädagogik. Qualitätsentwicklung. Professionalisierung. Standards. Schriften zur Medienpädagogik 54)

Medienpädagogik in pädagogischen Grenzfeldern – konzeptionelle Überlegungen am Beispiel des Maßregelvollzugs - Kamin, A.-M.; Meister, Dorothee M.; Sonnenschein, N. (Spannung? Potentiale! – Spannungsfelder des Digitalen und Bildungspotentiale)

Section I: Digital Humanities: The Role of the Digital in English Philology - Bartsch, Sabine; Mindt, Ilka (Anglistentag 2017 Regensburg. Proceedings)

Englischer Sprachwandel im Zeitalter von Digitalisierung und Innovation - Mindt, Ilka

How to Deal with Inaccurate Service Descriptions in On-The-Fly Computing: Open Challenges - Bäumer, Frederik Simon; Geierhos, Michaela (Proceedings of the 23rd International Conference on Natural Language and Information Systems)
The vision of On-The-Fly Computing is an automatic composition of existing software services. Based on natural language software descriptions, end users will receive compositions tailored to their needs. For this reason, the quality of the initial software service description strongly determines whether a software composition really meets the expectations of end users. In this paper, we expose open NLP challenges needed to be faced for service composition in On-The-Fly Computing.
Keywords: Requirements Extraction; Temporal Reordering of Software Functions; Inaccuracy Compensation

Improving Classifiers for Semantic Annotation of Software Requirements with Elaborate Syntactic Structure - Kim, Yeongsu; Lee, Seungwoo; Dollmann, Markus; Geierhos, Michaela (International Journal of Advanced Science and Technology)
A user generally writes software requirements in ambiguous and incomplete form by using natural language; therefore, a software developer may have difficulty in clearly understanding what the meanings are. To solve this problem with automation, we propose a classifier for semantic annotation with manually pre-defined semantic categories. To improve our classifier, we carefully designed syntactic features extracted by constituency and dependency parsers. Even with a small dataset and a large number of classes, our proposed classifier records an accuracy of 0.75, which outperforms the previous model, REaCT.
Keywords: Software Engineering; Natural Language Processing; Semantic Annotation; Machine Learning; Feature Engineering; Syntactic Structure

Monitoring für die Bahnhofsmissionen: Ein datengestütztes Instrument zur Organisationsentwicklung. Projektbeschreibung und Ergebnisdarstellung - Goller, Michael
Keywords: Bahnhofsmission; Survey Feedback; Monitoring